Comparative Systolic Blood Pressures in Healthy Cats Measured at Home and Different Times at a Veterinary Hospital using Doppler Ultrasonograph - Sastravaha, Amornrate; Rattanasrisomporn, Jatuporn; Roongsitthichai, Atthaporn (Journal of Mahanakorn Veterinary Medicine, 2021)
The purposes of the present study were to investigate the systolic blood pressure (SBP) of 30 healthy cats between at home and at hospital using Doppler ultrasonography at a veterinary hospital in Thailand, and to validate the appropriate resting period prior to re-measuring blood pressure. All the cats were measured for SBP at home (SBP0), then immediately upon arrival at the hospital (SBP1), 30 min after arrival (SBP2), and 60 min after arrival (SBP3). Each of measurements was triplicated at one-minute interval. The results revealed that mean SBP0, SBP1, SBP2, and SBP3 of the cats were 124.31±9.74, 167.61±18.21, 153.07±17.28, and 136.52±9.11 mmHg (P<0.05), respectively. In addition, the differences of SBP1, SBP2, and SBP3 from SBP0 were 34.83%, 23.14%, and 9.82% (P<0.001), respectively. In summary, blood pressure measurement in healthy cats should not be conducted abruptly upon arrival at the hospital since the SBP was > 30% higher than blood pressure at home. Therefore, SBP measurement at the hospital should be performed at least one hour after arrival in silent and private places to minimize the white coat effect, a situational hypertension, which may result in a misdiagnosis of true hypertension.